Way of Taoism : evolution, entrenchment or extinction. - Lim, Philip Jingyang. (2010)
Taoism has been bleeding devotees in the past few years, with challenges from within and without the religion. What was once Singapore's most widespread religion is fighting a battle of attrition in recent years, and many have pointed the finger at Taoism's fundamental principles of adopting a laid-back attitude towards life and therefore not putting much effort in converting new followers as being at the root of the problem. Reports have also said devotees are leaving Taoism for arguably more popular and mainstream religions such as Buddhism and Christianity, who have stepped up their game to draw followers into their fold.